Role of Insulin Resistance and Oxidative Stress in Hair Loss - Noor Qais Yaseen; Qutaiba Abdulkareem Qasim; Firas Fakhir Matrood (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Alopecia is a common cosmetic problem that affects over 50% of adults at some stage in their life, and It can lead to various psychological and social difficulties, especially in young people.Recent studies have suggested that insulin resistance and oxidative stress have a pathological role in hair loss. Objective: Despite the wide range of physiological variables that contribute to hair loss, there have been few studies that completely cover these problems. The current study directed to highlight the effect of insulin resistance(HOMA IR), oxidative stress (MDA nmol/ml and H2O2 μmol/L), and antioxidant marker(superoxide dismutase SOD) on diffuse hair loss in males and females in Basra Governorate. Methods:ninety-six patients with diffuse hair loss between the age of 16 and 42 years old as cases and fifty-three normal controlwere measured with serum concentrations of HOMA-IR, MDA,H2O2and SOD. Results: The statistical analysis revealed no significant difference between the groups in terms of HbA1C, fasting insulin, and HOMA IR (P value >0.05). Additionally, there was a statistically significant difference seen in oxidative marker H2O2, MDA and antioxidant marker SOD P value P < 0.05. Conclusion: The study found that an oxidative stress marker (MDA and H2O2), together with reduced SOD activity, is critical in developing diffuse hair loss. More studies are needed to validate these findings, evaluate the potential links between oxidative stress and insulin resistance, and look into other oxidative stress indicators in the pathology of diffuse hair loss.